The Sanctuary of Asklepios and Hygieia at Corinth - Waele, Ferdinand de (Analecta Gorgiana, 2009)
In this paper de Waele gives the excavation report for a medium-sized Asklepeion near the northern border of the Corinthian demos, providing a perspective on the smaller local temples of Asklepios